Correcting Precipitation Measurements Made with Geonor T-200B Weighing Gauges near the August-One Ice Cap in the Qilian Mountains, Northwest China - Zhao, Yanni; Chen, Rensheng; Han, Chuntan; Wang, Lei; Guo, Shuhai; Liu, Junfeng (Journal of hydrometeorology, 2021)
A precipitation observation network was constructed in a high-altitude area of the Qilian Mountains in northwest China, which contained 23 sets of instruments. Because 21 sets of instruments were surrounded by protective fences, a precipitation intercomparison experiment was carried out at the highest station (4651 m) of the observation network with the same configuration to study the impact of wind on precipitation measurements under this configuration and to develop a correction method suitable for the entire network. The 30-min measured precipitation from June 2018 to October 2019 was corrected by the World Meteorological Organization Solid Precipitation Intercomparison Experiment transfer functions, and their parameters were recalibrated with a local dataset. The results showed that the transfer functions fitted to the local dataset had a better performance than those using original parameters. Because of the influence of the experimental configuration on wind speed and direction, the root-mean-square error (RMSE) corrected with the original parameters increased by an average of 86%, but the RMSE adjusted by the new transfer functions decreased by 9%. Moreover, the resultant biases using new transfer functions were close to 0. The new coefficients of snowfall were derived by local measurements and applied to datasets from other sites within the Qilian Mountains observation network to evaluate their performances. The corrected snowfall at 21 stations increased by an average of 32.6mm, and the relative precipitation increment ranged from 6% to 26%. This method can be used to correct snowfall in the observation network under the nonstandard site configuration.